Modern aspects of sustainable development in context of global safety - Dyrda, V.I.; Volovyk, I.A. (Геотехнічна механіка, 2014)
The authors have considered modern scientific approaches to the problem of sustainable development of complex dynamic systems. Main factors of risks are generalized: anthropogenic, technogeneous and ecological. Some aspects of Darwin’s triad and the second law of thermodynamic are used to explain the problems of global safety. Автори розглянули сучасні наукові підходи до проблем сталого розвитку складних динамічних систем. Узагальнені головні фактори ризику: антропогенні, техногенні і екологічні. Деякі аспекти дарвінівської тріади та другий закон термодинаміки використані для пояснення аспектів глобальної безпеки. Авторы рассмотрели современные научные подходы к проблеме устойчивого развития сложных динамических систем. Обобщены главные факторы риска: антропогенные, техногенные и экологические. Некоторые аспекты дарвиновской триады и второй закон термодинамики использованы для объяснения аспектов глобальной безопасности.